2015
DOI: 10.1038/srep08019
|View full text |Cite
|
Sign up to set email alerts
|

Association of the immature platelet fraction with sepsis diagnosis and severity

Abstract: Management of Sepsis would greatly benefit from the incorporation of simple and informative new biomarkers in clinical practice. Ideally, a sepsis biomarker should segregate infected from non-infected patients, provide information about prognosis and organ-specific damage, and be accessible to most healthcare services. The immature platelet fraction (IPF) and immature reticulocyte fraction (IRF) are new analytical parameters of the complete blood count, that have been studied as biomarkers of several inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
50
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 35 publications
7
50
3
Order By: Relevance
“…In fact, a raise in the circulating IPF has been reported also in inflammatory conditions not associated with direct thrombotic risk, as in infectious disorders and even in sepsis, and moreover, we recently documented no impact of IPF levels on angiographic findings in a large unselected cohort of patients . In effect, in our population of patients with diabetes, the rate of patients with acute presentation inversely related with the levels of IPF suggesting that the dysregulations of thrombocytes turnover induced by diabetes could prevent the elevation of RPs previously reported in the settings of ACS.…”
Section: Discussionsupporting
confidence: 52%
“…In fact, a raise in the circulating IPF has been reported also in inflammatory conditions not associated with direct thrombotic risk, as in infectious disorders and even in sepsis, and moreover, we recently documented no impact of IPF levels on angiographic findings in a large unselected cohort of patients . In effect, in our population of patients with diabetes, the rate of patients with acute presentation inversely related with the levels of IPF suggesting that the dysregulations of thrombocytes turnover induced by diabetes could prevent the elevation of RPs previously reported in the settings of ACS.…”
Section: Discussionsupporting
confidence: 52%
“…Several studies have demonstrated the clinical utility of IPF in laboratory diagnosis of thrombocytopenia due to peripheral platelet destruction, particularly autoimmune thrombocytopenic purpura and thrombotic thrombocytopenic purpura [12,13]. The IPF was recently introduced as a novel diagnostic biomarker for infection and developing sepsis [14,15]. To our knowledge, however, no studies have evaluated the clinical value of IPF for coagulopathy or its prognostic value in patients with sepsis.…”
Section: Accepted Manuscriptmentioning
confidence: 96%
“…In other studies, an increased IPF was related to suspected bacterial infection and the severity of sepsis [15,27]. Although none of those studies examined the coagulation profile of participants in detail, IPF elevation suggested the onset of severe infection or sepsis.…”
Section: Accepted Manuscriptmentioning
confidence: 96%
See 1 more Smart Citation
“…Notably, the IPF% correlates with positivity of blood cultures,15 tends to increase before the onset of sepsis and is the only parameter whose values seem to vary independently from those of conventional coagulation tests 11. Finally, IPF% correlates with the scores conventionally used for assessing the severity of sepsis 13. The early increase of IPF may also be useful for understanding the underlying mechanisms of sepsis, thus allowing to identify a subset of patients with worse prognosis 14…”
Section: Introductionmentioning
confidence: 99%